MSME Product Photography Training Using Smartphones with DJPb Bali and Kreasiku Digital Marketing Agency - Decky Cipta Indrashwara; I Gede Fery Surya Tapa; I Nyoman Indra Kumara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The use of social media as a marketing platform has become the main strategy for Micro, Small, and Medium Enterprises (MSMEs) in expanding their market reach. However, limited knowledge and skills in product photography often become obstacles for MSMEs in creating attractive and quality visual content. In response to this challenge, a product photography training program using smartphones was organized by the Ditjen Perbendaharaan of Bali Province (DJPb Bali) in collaboration with several lecturers from the Universitas Pendidikan Nasional, and Kreasiku Digital Marketing Agency. This training aims to empower MSMEs to improve their product photography skills so that they can increase their competitiveness in the online market. This training method consists of a series of interactive workshop sessions involving MSME owners from various industrial sectors. The training material covers the basics of product photography, techniques for taking pictures using smartphones, as well as the use of AI in editing product photos. During the training, participants are encouraged to actively participate and practice directly the skills learned through practical sessions. The evaluation results showed a significant increase in participants' understanding of the basic concepts of product photography and the use of smartphones for taking pictures. Apart from that, participants also succeeded in developing photo editing skills and visual marketing strategies that are relevant to the characteristics of their products. Product photography training using smartphones with DJPb Bali is an effective step in empowering MSMEs to improve their product visualization and online marketing. By increasing these skills, it is hoped that MSMEs can be more competitive in the increasingly developing digital market.